Translanguaging Practices in Understanding English Tenses: Insights from Indonesian Undergraduate Students in English Education Programs - Ramadhani, Alfarozi Zidane; Widhiyanto, Widhiyanto (LPPM Universitas Pancasakti Tegal, 2026)
The English tenses present a significant grammatical challenge for Indonesian EFL learners due to the structural contrast between English and Bahasa Indonesia, which does not mark temporal distinctions through verb inflection. While conventional grammar instruction often relies on form-focused repetition, such approaches fail to build deep conceptual understanding necessary for authentic communication. This study investigates how translanguaging practices in peer-only group discussions support Indonesian undergraduate students in understanding English tense structures. Employing a qualitative descriptive design, this study examines a recorded peer group discussion among four fourth-semester students enrolled in an English Education program at a university in Indonesia. Data were analyzed using thematic analysis following Braun and Clarke's (2006) framework. Three themes were identified: translanguaging as scaffolding, negotiation of meaning, and benefits and challenges of peer translanguaging. The findings reveal that students spontaneously drew on Bahasa Indonesia to clarify, explain, and illustrate English tense concepts for peers, functioning as mutual scaffolding within Vygotsky’s Zone of Proximal Development. Translanguaging also served as a meaning negotiation tool, with varied outcomes depending on the conceptual accuracy of group members. Additionally, translanguaging fulfilled socio-emotional functions, fostering group cohesion and interpersonal care. However, a key challenge emerged: peer-only translanguaging cannot resolve false cognate errors when all members share the same L1 interference and no more capable interlocutor is present. These findings contribute empirical evidence of spontaneous peer translanguaging in grammar learning and suggest that English Education programs should recognize translanguaging as a legitimate and effective peer learning strategy, supported by teacher monitoring.